La aplicación de indicadores de evaluación por los docentes en la asignatura de ciencias naturales y el desarrollo de destrezas con criterios de desempeño en los estudiantes de noveno año de educación general básica del colegio nocturno de bachillerato Presidente Isidro Ayora período lectivo 2013-2014 - Espinosa Balcazar, Roberth Israel (2014)
Changes in the learning process and the inclusion in them of operating a new model for the development of skills with performance criteria and evaluation indicators set planning, teachers returned to the stage in the development of a model within committed individuals with troubleshooting and aware of the reality of their environment. The key evaluation indicators expressing the results that guarantee the achievement of the objectives are concrete evidence of learning outcomes, indicating the essential performance must demonstrate the student. The skills to express performance criteria knowhow with one or more comprehensive actions that establish relations with certain knowledge. This study is descriptive and explanatory, is aimed at teachers for examination and take action on the need to improve the teaching learning from skills to performance criteria and test development through indicators evaluation in the area of Natural Sciences, contrasting the reality of educational institutions and document Updating and Strengthening Basic Education Curriculum General therefore is entitled: THE APPLICATION OF EVALUATION INDICATORS FOR TEACHERS IN THE COURSE OF NATURAL SCIENCE AND SKILL DEVELOPMENT WITH PERFORMANCE CRITERIA IN THE NINTH YEAR STUDENTS OF GENERAL EDUCATION BASIC COLLEGE NIGHT HIGH SCHOOL PRESIDENT ISIDRO AYORA LECTIVO PERIOD 2013-2014. Was raised as a general objective: to analyze the application of indicators to evaluate the teachers of natural sciences, in order to check the development of skills with performance criteria students Ninth Year of Basic General Education of the Night College High School President Isidro Ayora academic year 2013-2014. The methods used for the development of this thesis report were, the inductive method, which allowed individuals diagnose problems encountered in the school, to get to determine the main problem; deductive method was needed to analyze the overall results; the analytical method allows the analysis of the information. Classification and comparison with the reality of the institution; and the synthetic method allowed writing and processing information coming to the formulation of conclusions and recommendations in the report of thesis; bibliographic and statistical method in gathering empirical information. To obtain information; surveys were conducted two teachers and fourteen freshmen year of General Basic Education; observation and record of a class of Natural Sciences and an assessment tool to check the development of skills with performance criteria. After the research and then analyzing the results, we have determined the following conclusions: the Natural Science teachers surveyed lack a clear understanding of the meaning of evaluation indicators and skills with performance criteria, these two being the foundation in the teaching-learning process which makes the application and affects development and subsequent verification of skills with performance criteria freshmen year of basic general education. • Keywords: Skills with performance criteria, evaluation indicators.